A Review on Design and Development of high Reliable Hybrid Energy Systems with Droop Control Techniques - G. Srinivasa Rao; K. Harinadha Reddy (Institute of Advanced Engineering and Science, 2016)
Hybrid Energy system is a combination of two or more different types of energy resources. Now a day this hybrid energy system plays key role in various remote area power applications. Hybrid energy system is more reliable than single energy system. This paper deals with high reliable hybrid energy system with solar, wind and micro hydro resources. The proposed hybrid system cable of multi mode operation and high reliable due to non communicated based controllers (Droop Characteristic Control) are used for optimal power sharing. size of battery can be reduced because hydro used as back up source and Maximum power point Tracking also applied to solar and wind energy systems.